1998
DOI: 10.1159/000021996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aging on Cortical and Trabecular Bone Response to Estradiol Treatment in Ovariectomized Rats

Abstract: Three groups (n = 15/group) of 6-, 12- and 30-month-old (mature, old and senescent animals, respectively) female Wistar rats on a diet (6 g/100 g BW/day) containing 0.8% calcium and 0.8% inorganic phosphorus were studied. Within each group, 10 rats were ovariectomized surgically and 5 injected s.c. with 17β-estradiol (E rats, 10 µg/kg BW/48 h) and 5 with solvent alone (OVX rats) from day 2 until day 60 after ovariectomy. Five other rats were sham-operated (SH rats) and received solvent only. All rats were kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Consistent with our findings in C57BL/6 mice, Gaumet et al (17) found that the skeletal response to estrogen was similar in young (6 month) versus old (12 month) rats, but the uterus of the old rats was much less responsive to estrogen as compared with the young rats. It is also of interest that recent data indicate that very low doses of estrogen can prevent bone loss in elderly postmenopausal women without significant uterine stimulation (18,19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our findings in C57BL/6 mice, Gaumet et al (17) found that the skeletal response to estrogen was similar in young (6 month) versus old (12 month) rats, but the uterus of the old rats was much less responsive to estrogen as compared with the young rats. It is also of interest that recent data indicate that very low doses of estrogen can prevent bone loss in elderly postmenopausal women without significant uterine stimulation (18,19).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, previous studies have found that in mature rats subcutaneous injections of E 2 (10 mg/kg/48 h) resulted in a distinct increase in uterine weight (21%) compared with sham-operated rats at doses that were less effective on bone, whereas similar doses of E 2 (18 mg/kg/day) given by subcutaneous pellets led to an increase in cancellous bone area with no increase of the uterine weight above the weight of the sham-operated rats (17,23). Also of interest is the study by Erben et al (24) in rats, where a dose of estrogen given by subcutaneous pellets (5.2 mg/kg/day) resulted in an increase in cancellous bone area with a concomitant decrease in uterine wet weight over the course of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical features of osteoporotic patients in bone remodeling were reported as follows. According to several reports, in patients with postmenopausal osteoporosis, the rate of trabecular bone loss is greater than that of normal subjects34; however, the rate of cortical bone loss is only slightly above normal 31. In contrast, Riggs and Melton11 reported that patients with senile osteoporosis showed a proportionate loss of cortical and trabecular bone and that the rate of bone loss was slightly higher than normal.…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by the insufficient decrease in mechanical properties in OVX rats as compared with sham‐operated rats at 12 weeks after the surgery. A previous report has shown that neither OVX nor E 2 replacement had a significant effect on tibial mechanical properties at 2 months after the surgery on 6‐, 12‐, and 30‐month‐old rats (30) . Another report also has shown that the decrease in femoral bone strength by OVX is not seen before 9 months after the surgery on 6‐month‐old rats (27) .…”
Section: Discussionmentioning
confidence: 97%